Association Between Recent Overnight Travel and Risk of Malaria: A Prospective Cohort Study at 3 Sites in Uganda. (4th June 2018) - Arinaitwe, Emmanuel; Dorsey, Grant; Nankabirwa, Joaniter I; Kigozi, Simon P; Katureebe, Agaba; Kakande, Elijah; Rek, John; Rosenthal, Philip J; Drakeley, Chris; Kamya, Moses R; Staedke, Sarah G
Abstract : At 3 sites in Uganda, recent overnight travel was associated with an increased incidence of malaria in cohort participants followed up for 1 year. Individuals who travel may represent a high-risk group that could be targeted for malaria control interventions. Abstract: Background: Human movement can undermine malaria control efforts. However, understanding of the association between travel and malaria infection in Africa is limited. We evaluated the association between recent overnight travel and malaria incidence in Uganda. Methods: All children aged 0.5–10 years and 1 adult living in 266 randomly selected households within 3 different regions of Uganda were followed up prospectively. Information on overnight travel was collected in 2015–2016. Malaria, defined as fever with parasites detected by microscopy, was measured using passive surveillance. Results: At least 1 overnight trip was reported by 64 of 275 (23.3%) participants in Walukuba, 37 of 317 (11.7%) in Nagongera, and 19 of 314 (6.1%) in Kihihi. Among individuals who traveled, the incidence of malaria was higher in the first 60 days after traveling, compared with periods without recent travel at all 3 sites (overall, 1.15 vs 0.33 episodes per person-year; incidence rate ratio, 3.53; 95% confidence interval, 1.85–6.73; P < .001). Risk factors for malaria within 60 days after overnight travel included young age (19.5% in children vs 4.9% in adults; odds ratio, 5.29; 95% confidence interval, 1.34–21.0; P = .02) and not using an insecticide-treated net during travel (18.0% for no use vs 4.1% for any use; 5.10; 1.07–24.5; P = .04). Conclusions: Recent overnight travel was associated with a higher incidence of malaria. Individuals who travel may represent a high-risk group that could be targeted for malaria control interventions, particularly use of insecticide-treated nets.